Formation of N2 bubbles along grain boundaries in (ZnO)1−x(GaN)x: nanoscale STEM-EELS studies. Issue 7 (4th February 2020) - Bazioti, Calliope; Olsen, Vegard S.; Kuznetsov, Andrej Y.; Vines, Lasse; Prytz, Øystein
Abstract : N2 -filled voids along grain boundaries were revealed by STEM-EELS, showing elemental redistribution and bonding re-arrangement in annealed (ZnO)1− x (GaN) x . Abstract : Direct evidence of N2 formation after annealing of (ZnO)1− x (GaN) x alloys was revealed. N2 was trapped by VZn+Ga -clusters, forming faceted voids along grain boundaries. This study shows that N–N bonding is a competitive path for nitrogen after annealing, in addition to the increasing Ga–N bonds, indicating that N in O substitution sites (NO ) is not a stable configuration.